Indigenous Peoples’ Problems in Argentina and Social Impacts of Native Forest Management - Luna, Claudia (2018)
The native peoples have recognized, in the legal system of the Argentine Republic, their property rights over the territories they traditionally occupy. Despite this, there is a profound difference between the regulations and the effective enjoyment and exercise of their rights. The objective of this work is to bring to light the following aspects: the current situation of the native peoples in Argentine Republic; the relationship between the State, the private sector and the indigenous communities; the intervention of the State in the face of complaints of irresponsible management of forest resources and the problems raised with regard to the transformation suffered by the corresponding native forests in order to raise awareness of an issue that has caused irreparable losses of natural, cultural and historical assets of the indigenous peoples. In this context, it is a fact that, for the indigenous communities that inhabit the native forests, the technological changes of the industrial society and the incursions of the actors of the market economy require a continuous adjustment in order to survive. The limited capacity to adapt to the demands of the non-indigenous society makes the changes affect the native communities in a special way. That is why these groups are at a crossroad that has worsened rapidly by the dramatic changes of their environment in recent years: the loss of biological diversity erodes their material base for survival, and the loss of cultural traditions weakens their base of values and social structures.